Primary Leptomeningeal Oligodendroglioma, IDH-Mutant, 1p/19q-Codeleted - Ballester, Leomar Y.; Dunbar, Erin; Guha-Thakurta, Nandita; Henson, John W.; Chandler, Howard; Watkins, Jeremiah; Fuller, Gregory N. (Frontiers in Neurology, 2018)
We present a case of a 43-year-old woman with a history of headaches and blurry vision. Ophthalmologic examination identified papilledema. MR imaging demonstrated a right parietal region mass with patchy areas of contrast enhancement and focal calcifications. Intraoperative examination and exploration revealed an extra-axial mass with no apparent parenchymal involvement. Microscopic examination revealed solid sheets of tumor cells with clear cell cytologic features and no discernable intra-parenchymal tumor component. Molecular studies demonstrated the presence of IDH1 IDH1 c.395G>A p.R132H and CIC c.601C>T p.R281W mutations and 1p/19q codeletion. The radiographic features, gross appearance, and microscopic and molecular characteristics of the mass support the diagnosis of primary leptomeningeal oligodendroglioma, IDH-mutant, 1p/19-codeleted. This case represents one of a very few reported instances of molecularly-defined solitary, primary, intracranial oligodendroglioma, without definitive involvement of the brain parenchyma.